Relationship between receipt of substitutable for-fee vaccines and completion of the expanded programme on immunisation: a cross-sectional study in Fujian, China. Issue 7 (20th July 2017) - Wu, Jiang-Nan; Li, Da-Jin; Zhou, Yong; Du, Mei-Rong; Piao, Hai-Lan
Abstract : Objective: The aim of this study was to evaluate the relationship between receipt of the substitutable-for-fee vaccines (SFV) and completion of the expanded programme on immunisation (EPI). Design and settings: A cross-sectional study was conducted in Fujian province, China. Participants: Children who were born from 1 September 2009 to 31 August 2011, and who had been residing in the township for at least 3 months, were randomly recruited from 34 townships. Main outcomes measures: Outcomes were completion rate of the EPI and coverage rate of the SFV. Results: The study included 1428 children, of whom 1350 (94.5%) finished the EPI and 282 (19.7%) received at least one dose of the SFV. Administration of the SFV was associated with an increased likelihood of completing the EPI (OR=3.2, 95% CI 1.3 to 7.6 in the total sample and OR=4.0, 95% CI 1.7 to 9.6 in the subsample of children in regions with the SFV accessibility). The impact of the SFV administration on completion of the EPI was larger among children whose parents have junior school education or less (97.8% and 97.9% vs 92.5% and 91.9%, both p<0.001) and among those with a timely hepatitis B vaccine first dose (98.5% vs 94.0%, p<0.001). Conclusions: Receipt of SFV is associated with increased likelihood of completion of the EPI in Fujian, China.